A Game PEKA untuk Trauma Healing Pada Anak Pasca Bencana di Kabupaten Banyumas - Rafika Bayu Kusumandari; Suripto Suripto; Sony Zulfikasari (JTP - Jurnal Teknologi Pendidikan, 2019)
The research objective is the use of PEKA games for healing trauma in disaster areas. This research uses discuss "Qualitative Research". Research results: this research was conducted in the village of Klahang, Sokaraja District, Banyumas Regency. Where there was a fire accident at the Bakso stall next to the TPQ during the learning process. This makes children overcome trauma. Of the 34 children there were 14 children who were used as research respondents. For the data collection process carried out for 7 days. There are 4 children who suffered severe trauma, 5 moderate trauma and 5 minor trauma. Children who were severely traumatized when it happened were near a meatball stall that exploded and then caught fire. Conclusion: this learning game is effective for overcoming learning in disaster areas and for reducing trauma in post-disaster children.